CRISPR‐TAPE: protein‐centric CRISPR guide design for targeted proteome engineering - Daniel Paolo Anderson; Henry James Benns; Edward William Tate; Matthew Andrew Child (Molecular Systems Biology)
Abstract Rational molecular engineering of proteins with CRISPR‐based approaches is challenged by the gene‐centric nature of gRNA design tools. To address this, we have developed CRISPR‐TAPE, a protein‐centric gRNA design algorithm that allows users to target specific residues, or amino acid types within proteins. gRNA outputs can be customized to support maximal efficacy of homology‐directed repair for engineering purposes, removing time‐consuming post hoc curation, simplifying gRNA outputs and reducing CPU times.